Consumer Psychology of Tourism, Hospitality and Leisure Volume 2 - Mazanec, J. A (CABI, 2014)
This volume is dedicated to a series of research reports presented at the Second Symposium on the Consumer Psychology of Tourism, Hospitality and Leisure (CPTHL) in Vienna, Austria, during 6 and 9 July, 2000.